Knowledge, attitudes and practice towards Covid-19 among the Orang Asli elderly in Peninsular Malaysia - Rosnon, Mohd Roslan; Zuhairi, Mohd Haikal; Abdul Razak, Muhammad Afiq; Jalaludin, Muhamad Luqmanudin; Ibrahim, Rahimah (Human Resource Management Academic Research Society, 2022)
The COVID-19 pandemic has impacted the globe since 2020, and the indigenous people are not excluded, including the Malaysia Orang Asli. They were already among the most vulnerable communities, even before the pandemic, thus, have a higher risk: perhaps the elderly groups are even at the great threat from this alarming catastrophe. A total of 305 respondents from all the 18 Orang Asli sub-groups were involved in this study, with a minimum age of 50 year-olds. Gathering information was done by quantitative data collection using survey techniques. The findings revealed four out of 13 questions about the virus details have the highest number on the misleading details, while the rest are satisfactory. The respondents were not sure if the pandemic can be controlled in general, however, had a strong confidence in the Malaysian government’s responses towards the pandemic. The precautions suggested to minimize the risk were also practised, however, most respondents were not sure when it comes to the specific hygiene precautions. Thus, better-targeted approaches to educating the Orang Asli communities, especially the elderly should be strengthened, to ensure they are not be outdated from crucial information, thus ensuring their wellbeing during the pandemic time.